Miniaturized Wilkinson power divider with extra coupled line section for compensation. Issue 8 (August 2015) - Wang, Xiaolong; Ma, Zhewang; Sakagami, Iwata; Mase, Atsushi; Yoshikawa, Masayuki
ABSTRACT: In this article, λ/4 coupled microstrip line section is used in the design of two‐way miniaturized Wilkinson power divider. To compensate the phase velocity difference in λ/4 coupled microstrip line section, extra coupled line section is connected between λ/4 coupled line section and two output ports. Due to no lumped elements have been used, this compensation method not only provides compact circuit size and easy fabrication but also suitable for high frequency operation. Design equations are derived from even‐ and odd‐mode analyses. Several design examples show that: (i) Extra coupled line section could compensate arbitrary coupling strength in λ/4 coupled microstrip line section, and its coupling strength also can be adjusted arbitrarily. (ii) Considering the bandwidths of S22, S33, and S32, the coupling strength of λ/4 coupled microstrip line section plays a major role, the bandwidths become narrower as coupling strength increased. Compared with the conventional λ/4 coupled line section model in homogeneous medium, the bandwidth differences are very small, and they can be negligible. In other word, the proposed model could provide the same performance for inhomogeneous medium application. (iii) The length of extra coupled line section becomes longer as coupling strength of λ/4 coupled line section increased, however, it becomes shorter as coupling strength of extra coupled line section increased. In experiment, one circuit was fabricated, the measurement results showed good agreement with theoretical results. © 2015 Wiley Periodicals, Inc. Microwave Opt Technol Lett 57:1869–1873, 2015